Sneak Path-Aware Reliability-Based Iterative Majority-Logic Decoding Algorithms for LDPC Codes in ReRAM Systems - Kong, Lingjun; Qi, Yingnan; Liu, Haiyang; Meng, Chao (IEEE communications letters, 2025)
The performance of classical channel decoding algorithms in resistive random access memory (ReRAM) channels is severely degraded due to the sneak path interference (SPI) caused by the crossbar array structure. In this letter, we first propose a sneak path-aware reliability-based iterative majority-logic decoding (SPR-IMLGD) algorithm for low-density parity-check (LDPC) codes by integrating the sneak path information into reliability metrics. In particular, we introduce the sneak path distance, derived from the associated sneak path probability, which provides a desirable characterization of the presence and extent of sneak paths within a given memory cell. Moreover, we present an enhanced version of the SPR-IMLGD algorithm (ESPR-IMLGD) that further improves the error correction performance. We also optimize the calculation of sneak path distance, ensuring that the SPR-IMLGD and ESPR-IMLGD algorithms have the same level of computational complexity. Simulation results demonstrate that the SPR-IMLGD and ESPR-IMLGD algorithms can achieve better performance with lower computational cost compared with the existing methods.